Defining Marriage Readiness: A Narrative Review of Influencing Factors and Perspectives - Nabila Layalia Septiasari; Kartika Sari Dewi (Proceedings of the 1st International Conference on Social Science (ICSS), 2025)
The phenomenon of declining marriage rates, increasing divorce rates, and the shifting perceptions of individuals toward the institution of marriage indicate that awareness of the importance of marriage readiness remains suboptimal within society. Therefore, marriage preparation is a crucial aspect that cannot be overlooked, as it reflects an individual's ability and skills to fulfill marital roles and responsibilities. Marital readiness plays a vital role in navigating the various challenges and dynamics of married life. This study aims to identify and synthesize the factors that influence marriage readiness and to explore the concept of marriage readiness based on various sources. The research method is literature study in the form of narrative review. The literature was searched using relevant keywords, published within the last 10 years across various academic database including Scopus, ScienceDirect, ProQuest, and Google Scholar. A total of 10 studies that met the inclusion criteria were selected based on their relevance to the topic and their contribution to the conceptual understanding of marriage readiness. Based on the literature review conducted in this study, it is evident that marriage readiness is influenced by various factors, including age and developmental stage, financial stability, psychological readiness, physical and biological condition, sociocultural factors, spiritual and moral considerations, interpersonal skills, and knowledge about family life. The findings of this study are expected to contribute to the development of educational efforts and appropriate intervention designs in premarital counseling programs, aiming to enhance the quality of marriage in the future.